Hospitalidade: um estudo de caso do Hospital UNIMED Nordeste RS - Quevedo, Mariana Fasolo (My University, 2014)
The concept of Hospitality is very broad, ranging from commerce and market to people and their relationships. It is related to exchange relations, in the economical, social, and psychological fields. For health institutions to be competitive, they have to be aware of human exchanges, and using these for their benefit, through differentiated services to be offered to their clients. Keeping these concepts in mind, a literature review was made, related to Hospitality in hospital environment - hospitality, management, hospitals, and competitivity - to grasp a better understanding of the subject. Besides these themes, aspects related to the analyzed variables (leisure, food services, and architecture) were also researched. The field research - case study - focused on the Hospital Unimed Nordeste RS, in Caxias do Sul - RS, Brazil, aiming to the understanding on how Hospitality is being managed, and if it is resulting on competitivity to the institution, through the analysis of the three chosen variables. Data collection has had three sources - direct observation, interviews, and questionnaire - making it possible to answer comparisons. Using data crossing from the three evidence sources and the observed theory, result analysis was developed, focused on procedure execution and competitivity.
A hospitalidade tem uma definição ampla, que abrange não somente o setor comercial e o mercado, mas também as pessoas e as relações entre elas. Envolve relações de troca, nos âmbitos econômico, social e psicológico. As instituições de saúde para serem competitivas devem estar atentas às trocas humanas, a fim de usá-las a seu favor, através do oferecimento de serviços diferenciados aos clientes. Tendo em vista esses conceitos, utilizou-se revisão bibliográfica em assuntos pertinentes à prática da hospitalidade em hospitais - hospitalidade, gestão, hospitais e competitividade - a fim de promover um melhor entendimento do tema. Além desses, os aspectos correspondentes às variáveis a serem analisadas posteriormente foram abordados, sendo eles o lazer, a alimentação e a arquitetura. A pesquisa realizada - estudo de caso - se deu no Hospital Unimed Nordeste RS, em Caxias do Sul, Rio Grande do Sul, Brasil, com o objetivo de estudar como a hospitalidade está sendo gerida e se ela gera competitividade à instituição, aravés da análise das três variáveis escolhidas. A coleta de dados teve três fontes de evidências - observação direta, entrevistas e aplicação de questionários - o que determinou a possibilidade de afirmação e de confronto de respostas. Através do cruzamento dos dados obtidos nas três fontes de evidências com a teoria observada, desenvolveu-se a análise dos resultados, focada na realização de procedimentos e na competitividade.
Keywords: Turismo; Hospitalidade; Gestão hospitalar; Competitividade; Caxias do Sul (RS); Tourism; Hospitality; Hospital management; Competitivity; Caxias do Sul (Brazil); Alimentação hospitalar; Hospital